Vascular and Macrophage Heme Oxygenase-1 in Hypertension: A Mini-Review - Martínez-Casales, Marta; Hernanz, Raquel; Alonso, María J. (Frontiers in Physiology, 2021)
Hypertension is one predictive factor for stroke and heart ischemic disease. Nowadays, it is considered an inflammatory disease with elevated cytokine levels, oxidative stress and infiltration of immune cells in several organs including heart, kidney and vessels, which contribute to the hypertension-associated cardiovascular damage. Macrophages, the most abundant immune cells in tissues, have a high degree of plasticity that is manifested by polarization in different phenotypes, being the most known M1 (proinflammatory) and M2 (anti-inflammatory). In hypertension, M1 phenotype predominates, producing inflammatory cytokines and oxidative stress, and mediating many mechanisms involved in the pathogenesis of this disease. The increase in the renin-angiotensin system and sympathetic activity contributes to the mobilization of macrophages and to its polarization to the pro-inflammatory phenotype. Heme oxygenase-1 (HO-1), a phase II detoxification enzyme responsible for heme catabolism, is induced by oxidative stress, among others. HO-1 has been shown to protect against oxidative and inflammatory insults in hypertension, reducing end organ damage and blood pressure, not only by its expression at vascular level, but also by modulating macrophages towards anti-inflammatory phenotype. The regulatory role of heme availability for the synthesis of enzymes involved in hypertension development, such as cyclooxygenase or nitric oxide synthase, seems to be the responsible for many of the beneficial effects of HO-1; additionally, the antioxidant, anti-inflammatory, antiapoptotic, and antiproliferative effects of the end-products of its reaction, carbon monoxide, biliverdin/bilirubin and Fe2+, would also contribute. In this review, we analyze the role of HO-1 in hypertensive pathology, focusing on its expression in macrophages.